The conventional and new aspects for cerebrolysin application - Chitaeva, G. E.; Nikiforova, A. N.; Sapon, N. A. (Ukrainian Neurosurgical Journal, 2005)
The article is devoted to cerebrolysin application in different fields of medicine: neurosurgery, neurology, psychiatry. Cerebrolysin is a medicine that contains low molecular active peptides and is used widely for traumatic, vascular and degenerative nervous system diseases treatment. Cerebrolysin has an expressive neuroprotective and neurotrophic activity (that is similar to natural nervous growing factor), it improves the patients life quality, moving and mental functions and the capacity to control the degenerative disease progress; and it differs due to the long effect, that is maintained up to 6 months after the therapy course has been finished, also it practically has no side reactions.